Gestión administrativa en el departamento de Recursos Humanos del Ministerio de Transporte y Obras Públicas - Vargas Mera, Jomayra Lilibeth (2020)
The administrative management of human resources allows the members that make up the company or entity in walking each of their efforts towards the achievement of the objectives based on administrative principles such as organization, planning, direction and control depending on each of their activities , so that each employee is placed in the appropriate position and has the academic training and experience necessary to perform the tasks entrusted to them in an efficient and effective way to achieve the organization's goals. The correct management of human resources allows an increase in competitiveness, helps to overcome a productivity crisis, increases the pace of work and adapts to social, cultural, demographic and educational changes; obtaining a competitive advantage through their skills, knowledge and capabilities of each of the talents that can be combined and deployed to carry out the tasks effectively, this research is based on the identification of problems around the management of the human resources department of the Ministry of Transport and Public Works located in the city of Babahoyo, being one of the areas of greatest conflict, these problems derive from the recruitment and selection processes of personnel, the lack of a performance evaluation, lack of induction and training to the new staff, job burnout, and poor leadership.